Foreword: Special section on the Eurographics Workshop on Visual Computing for Biology and Medicine (EG VCBM) 2020. (December 2021) - Kozlíková, Barbora; Krone, Michael; Nieselt, Kay; Raidou, Renata G.; Smit, Noeska N.
Graphical abstract: Highlights: VCBM is the Eurographics Workshop on Visual Computing for Biology and Medicine. We address application-oriented visual computing research. This is includes visualization, visual analytics, image processing, and HCL. This section contains extended papers from VCBM 2021 and completely new articles.